As contradi????es entre o discurso oficial e o discurso sobre a pr??tica do supervisor de ensino no programa S??o Paulo faz escola - Souza, Ana Maria de (2011)
This study is aimed at understanding the role assigned by the S??o Paulo's Education Secretariat to the Supervisor of Education of educational system, in the implementation of the "S??o Paulo's school program". Regarded as an element of mediation and connection between the upper structure of the S??o Paulo's Education Secretariat and the teaching units, which means to connect the public policies to the schools' educational proposals, the Supervisor of Education experience the contradictions between the official discourse, which presumes proximity to the school management and, as a consequence, to its pedagogical actions and the actual practice, that imposes them an administrative burden and a lot of paperwork. By analyzing the literature on school supervision, the legal rules and duties of the Supervisor of Education, the documents that established the educacional reform in the public schools and also by means of interviews with Supervisor, we sought to examine the consequences of the managerial vision of education with its political accountability and meritocracy in the school management and in the job of the Supervisor of Education. The analysis of the empirical data collected, reinforced the initial hypothesis that there is a discrepancy between the discourse of the S??o Paulo's Education Secretariat, which is presented in the legal and institutional documents, and the discourse of the occupants of the position of Supervisor of Education, about the supervising practice on educational activities and on the role reserved for the category in the implementation of the "S??o Paulo's School Program".